(untitled) (International Journal of Physiotherapy, 2015)
Background: Carpal tunnel syndrome (CTS) is a constellation of symptoms associated with compression of the median nerve at the wrist in carpal tunnel. The Purpose of this study is to find the comparative effective of carpal bone mobilization and neural mobilization in improving pain, Functional Status and Symptom Severity in patients with CTS. Method: An experimental study design, 30 subjects with carpal tunnel syndrome were randomized into 2 groups with 15 subjects each in Group A and Group B. Subjects in Group A received carpal bone mobilization and subjects in Group B received median nerve mobilization. The duration of intervention was for two weeks. Outcome measurements such as pain using VAS, The Functional Status Score (FSS) and Symptom Severity Score (SSS) using the Boston’s questionnaire for CTS were measured before and after two weeks of intervention. Results: Analysis using paired ‘t’ test found that there is a statistically significant improvement (p<0.05) in pain, Functional Status score and Symptom Severity score within the groups. Comparative analysis using independent ‘t’ test found that there is no statistically significant difference in improving pain, Functional Status score and Symptom Severity score between both the groups. Conclusion: It is concluded that median nerve mobilization and carpal bone mobilization shown to be effective on improving pain, Functional Status and Symptom Severity in the treatment of patients presenting with carpal tunnel syndrome. However there is no significant difference in improvements obtained between the neural mobilization and carpal bone mobilisation.